Confiscation of Corruptor Assets Based UU 8 Year 2010 about Prevention and Eradication Of Money Laundering In National Criminal Law System - Rihantoro Bayuaji; M. Hidayat (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2017)
Confiscation of corruptor assets cannot be performed arbitrarily. It must adhere to the spirit of the TPPU Law, which means that law enforcement officers in seizing assets of the offender is still obliged to refer to the philosophy of TPPU Law to track the wealth of crimes. It means the Confiscation of assets using legal instruments of TPPU law shall be proven in predicate crime. Related to principle of justice, corruption case happened to Irjend. Pol. Djoko Susilo is one example whose assets were deprived under the pretext of using the TPPU Law as a basis for confiscation which ultimately deprived. However, it turned out that in the law enforcement process, some of his assets could not be proven to obtained from a crime or not. Obviously law enforcement clearly crashed human values, and Human Rights (HAM), which in fact the whole values are part of the value of justice, especially the dignified justice that is part of the Pancasila philosophy. In the future, law enforcement obliged to respect human rights.